PENERAPAN TERAPI ABA (APPLIED BEHAVIOR ANALYSIS) DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI VERBAL ANAK DENGAN DISABILITAS MENTAL SEDANG “SMR” DI KELURAHAN SUKALUYU KECAMATAN CIBEUNYING KALER KOTA BANDUNG - Nasril, Wahyudi (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2014)
AbstractThis article based on result of the research regarding application of Applied Behavior Analysis (ABA) Therapy in improving verbal communication skills for child with moderate mental disabilities called “SMR”. The aim of this research; how far the implementation of Applied Behavior Analysis (ABA) Therapy can increase verbal communication skills for child with moderate mental disabilities. This research uses a Single Subject Design and the research of hypotesis “is the application of Applied Behavior Analysis (ABA) Therapy can improve verbal communication skills for child with moderate mental disabilities called “SMR”?. The hypothesis test, using two standard deviation procedure, and then based on the measurement results obtained by mean difference between baseline phase 1 to phase 2 are 10.86. This value is higher than 2 standard deviations of mean in the phase baseline 1 is 8.02. The meaning that interventions were performed are significant to improve verbal communication skills for child with moderate mental disabilities called “SMR”.Keywords: child with moderate mental disabilities, verbal communication skills, Applied Behavior Analysis (ABA) Therapy AbstrakArtikel ini didasarkan pada hasil penelitian tentang penerapan Terapi Applied Behavior Analysis (ABA) dalam meningkatkan keterampilan komunikasi verbal anak dengan disabilitas mental sedang